2021
DOI: 10.1038/s41388-021-01897-0
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone suppresses immune evasion by inducing GR/STAT3 mediated downregulation of PD-L1 and IDO1 pathways

Abstract: T cell exhaustion plays critical roles in tumor immune evasion. Novel strategies to suppress immune evasion are in urgent need. We aimed to identify potential compounds to target T cell exhaustion and increase response to immune checkpoint inhibitors (ICIs). Differentially expressed genes (DEGs) were identified between tumors with different immune evasion potential by comparing the transcriptome data. DEGs were then analyzed in the Connectivity Map (CMap) platform to identify potential compounds to increase re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 48 publications
2
36
0
Order By: Relevance
“…As previously mentioned, PD-L1 is also upregulated in cancer cells by pro-inflammatory cytokines, such as IFNγ, TNF-α, and IL-6 [ 125 , 126 , 127 ]. Surprisingly, recent data suggest that treating tumor cell lines with GC promotes anti-tumor activity by decreasing PD-L1 expression [ 128 ]. In contrast, GCs induce PD-L1 expression in human DCs through transcription of a GR target gene, GC-induced leucine zipper (GILZ).…”
Section: Gc and Pd-1/pd-l1 Pathways In Health And Cancermentioning
confidence: 99%
“…As previously mentioned, PD-L1 is also upregulated in cancer cells by pro-inflammatory cytokines, such as IFNγ, TNF-α, and IL-6 [ 125 , 126 , 127 ]. Surprisingly, recent data suggest that treating tumor cell lines with GC promotes anti-tumor activity by decreasing PD-L1 expression [ 128 ]. In contrast, GCs induce PD-L1 expression in human DCs through transcription of a GR target gene, GC-induced leucine zipper (GILZ).…”
Section: Gc and Pd-1/pd-l1 Pathways In Health And Cancermentioning
confidence: 99%
“…The molecular mechanism may be related to the regulation of PI3 and S100A8 6 . Xiang et al 1 also adopted this strategy; they identified a group of compounds that may simultaneously inhibit PD-L1 and IDO1, and among them, dexamethasone was the optimal drug. The strategy of drug repurposing has also played an important role in the COVID-19 pandemic 7 .…”
Section: Drug Repurposing a New Direction For Pharmaceutical Researchmentioning
confidence: 99%
“…Dexamethasone-mediated transcriptional suppression of PD-L1 and IDO1 depended on the nuclear translocation of the GR/STAT3 complex. Their study suggested that dexamethasone could be used as a sensitization reagent for immune checkpoint inhibitors 1 .…”
Section: Drug Repurposing a New Direction For Pharmaceutical Researchmentioning
confidence: 99%
See 2 more Smart Citations